IMPLEMENTASI PRINSIP ISLAMIC CORPORATE GOVERNANCE DALAM PEDOMAN AMAL USAHA KESEHATAN - Berkah, Dian (Ahkam: Jurnal Hukum Islam, 2017)
Moslem scientists. Many analyze the corporate governance within the perspective of Moslem by which it comes up with a term of Islamic Corporate governance. The next development of corporate governance is the emergence of good governance in clinic or hospital which is called as clinical governance. So far, there has not been any study dealing with how good governance is implemented in a Islamic clinic. This study, therefore, is an effort to scrutiny the implementation of the principles in Islamic Corporate governance at Pedoman Amal Usaha Kesehatan Muhammadiyah. Kata kunci: Corporate governance, Islamic Perspective, Pedoman Amal Usaha Kesehatan